The Democracy reader classic and modern speeches, essays, poems, declarations, and documents on freedom and human rights worldwide - Ravitch, Diane; Thernstrom, Abigail M. 1936- (HarperCollins, 1992)
Classic and modern speeches, essays, poems, declarations, and documents on freedom and human rights worldwide--Subtitle.